2012
DOI: 10.1007/s00249-012-0850-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the lung surfactant protein B construct Mini-B on lipid bilayer order and topography

Abstract: The hydrophobic lung surfactant protein, SP-B, is essential for survival. Cycling of lung volume during respiration requires a surface-active lipid–protein layer at the alveolar air–water interface. SP-B may contribute to surfactant layer maintenance and renewal by facilitating contact and transfer between the surface layer and bilayer reservoirs of surfactant material. However, only small effects of SP-B on phospholipid orientational order in model systems have been reported. In this study, N-terminal (SP-B8–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…One possibility that has been considered is that the observed disruption of mechanical orientation induced by SP-B fragments might reflect interactions between the peptide and randomly oriented bilayers, at the hydration stage of sample preparation, that then interfered with flattening of the bilayers when orientational constraints were subsequently applied through the stacking of mica support plates [42]. Thus while the perturbation of mechanically oriented bilayers does provide some insight into interactions between SP-B fragment peptides and surfactant model bilayers, the constraints imposed by mechanical orientation may preclude observation of more dynamic perturbations of bilayer orientation or flatness by amphipathic peptides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility that has been considered is that the observed disruption of mechanical orientation induced by SP-B fragments might reflect interactions between the peptide and randomly oriented bilayers, at the hydration stage of sample preparation, that then interfered with flattening of the bilayers when orientational constraints were subsequently applied through the stacking of mica support plates [42]. Thus while the perturbation of mechanically oriented bilayers does provide some insight into interactions between SP-B fragment peptides and surfactant model bilayers, the constraints imposed by mechanical orientation may preclude observation of more dynamic perturbations of bilayer orientation or flatness by amphipathic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the extent to which different SP-B fragments and constructs interfere with mechanical bilayer organization suggest that such peptides can perturb bilayer surface geometry [41], [42]. In studies using bilayers deposited on mica plates, SP-B 8–25 and SP-B 63–78 were both found to promote the formation of bilayer populations with bilayer normal directions distributed over a range of angles with respect to the mechanically-oriented bilayer normal [41], [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pake quadrupole doublets split by half of the corresponding oriented sample doublet splittings. Doublets in the oriented component of the spectrum also broaden in a way consistent with increased mosaic spread [55]. The presence of SP-B (1–25,63–78) thus appears to disrupt the mechanical orientation in a small fraction of the bilayer material.…”
Section: Resultsmentioning
confidence: 76%
“…The presence of SP-B (1–25,63–78), a fragment which contains the N-terminal 7 residues as well as the first and last helices of SP-B, caused a substantial effect on the 2 H NMR splittings and hence acyl chain orientational order, particularly deep in the bilayer ( Table 1 ). The magnitude of the SP-B (1–25,63–78)-induced effect was particularly striking when compared to the effect of SP-B (8–25,63–78) [55], i.e. an identical peptide except for the absence of residues 1–7.…”
Section: Discussionmentioning
confidence: 88%